2006
DOI: 10.1145/1119479.1119481
|View full text |Cite
|
Sign up to set email alerts
|

Nontermination inference of logic programs

Abstract: We present a static analysis technique for non-termination inference of logic programs. Our framework relies on an extension of the subsumption test, where some specific argument positions can be instantiated while others are generalized. We give syntactic criteria to statically identify such argument positions from the text of a program. Atomic left looping queries are generated bottom-up from selected subsets of the binary unfoldings of the program of interest. We propose a set of correct algorithms for auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Methods to detect non-termination automatically have for example been studied for term rewriting (e.g., [11,19]) and logic programming (e.g., [18]). We are only aware of two existing tools for automated non-termination analysis of Java: The tool Julia transforms JBC programs into constraint logic programs, which are then analyzed for non-termination [20].…”
Section: Introductionmentioning
confidence: 99%
“…Methods to detect non-termination automatically have for example been studied for term rewriting (e.g., [11,19]) and logic programming (e.g., [18]). We are only aware of two existing tools for automated non-termination analysis of Java: The tool Julia transforms JBC programs into constraint logic programs, which are then analyzed for non-termination [20].…”
Section: Introductionmentioning
confidence: 99%
“…We compared our tool with N T I [10], the only other non-termination analyzer for logic programs. We have shown that our approach improves on the results of N T I and that we are able to prove non-termination of new classes of programs.…”
Section: Resultsmentioning
confidence: 99%
“…All programs contain between 2 and 15 clauses, except for binary4, which contains 41 clauses. The only other non-termination analyzer, N T I [10], proves non-termination for about 95% of the benchmark programs. Table 1 shows our experimental evaluation on this benchmark using LP-check with pruning, with 4 as a repetition number.…”
Section: Benchmark Of Termination Problemsmentioning
confidence: 99%
See 2 more Smart Citations